(untitled) (GEOgraphia, 2025)
Population growth has driven horizontal expansion in cities. Urban sprawl when unrestrained can cause several problems in environmental and socioeconomic segments. For medium-sized cities, such as Montes Claros/MG, this is already a fact. Therefore, understanding how expansion occurs spatially in the city is crucial for urban planning, especially regarding urban land use planning. Therefore, a simplified mapping of classes with potential for urban expansion for Montes Claros was elaborated and linear regression models were applied to understand which variables explained the distribution of these classes. Three classes were obtained: area with urban potential, area with potential for expansion, area not suitable for expansion. The area with urban potential was explained by the variable’s residents, water, income, unoccupied, occupied, vegetation, and altitude, and obtained an R² of 0.89 (p-value < 0.05). While the class area with expansion potential was explained by the variables not occupied, vegetation, and altitude (R² = 0.93 and p-value < 0.05). The unsuitable area was explained by altitude and relief (R² = 0.84 and p-value < 0.05). Socioeconomic and physical variables explained the spatial distribution of potential classes for urban expansion in Montes Claros. This methodology presents itself as a crucial tool for urban planning.